2020
DOI: 10.1007/s11904-019-00480-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Integrase Inhibitors for HIV Treatment

Abstract: Purpose of the review-The complex multistep life-cycle of HIV allows it to proliferate within the host and integrate its genome in to the host chromosomal DNA. This provirus can remain dormant for an indefinite period. The process of integration, governed by integrase (IN), is highly conserved across the Retroviridae family. Hence, targeting integration is not only expected to block HIV replication but may also reveal new therapeutic strategies to treat HIV as well as other retrovirus infections.Recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 112 publications
0
8
0
4
Order By: Relevance
“…Limitations to this study include that our analysis was restricted to PWH during chronic infection with low baseline CD4 + counts, limiting inference for patients today. Given comorbidity-free life expectancy is increased with early ART administration and rapid viral decline with current regimens that include integrase inhibitors [ 48 , 49 ], investigating whether Gal-9 still predicts NAEs following early modern ART intervention is warranted. Although Gal-9 was not significantly associated with NAEs at baseline, the effect size was notably consistent with our other findings and may be because of its strong link with viremia and immune suppression [ 9 , 12 , 34 ], as well as insufficient plasma for many participants at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to this study include that our analysis was restricted to PWH during chronic infection with low baseline CD4 + counts, limiting inference for patients today. Given comorbidity-free life expectancy is increased with early ART administration and rapid viral decline with current regimens that include integrase inhibitors [ 48 , 49 ], investigating whether Gal-9 still predicts NAEs following early modern ART intervention is warranted. Although Gal-9 was not significantly associated with NAEs at baseline, the effect size was notably consistent with our other findings and may be because of its strong link with viremia and immune suppression [ 9 , 12 , 34 ], as well as insufficient plasma for many participants at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…INSTIs bind to the catalytic core domain of the viral integrase to inhibit binding of the enzyme to the double-stranded DNA of the host. Since no equivalent homologs of integrase are known to exist in humans, INSTIs are generally believed to have limited off-target effects (68). Recent computational work, however, demonstrated that INSTIs could potentially interact with domesticated transposases, such as recombination activating gene 1 (RAG1), which is known to be involved in antibody and T-lymphocyte receptor V(D)J recombination.…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%
“…This therapeutic cocktail was formulated in a solvent mixture of 10% ethanol, 30% polyethylene glycol 400, and 60% Phosal 50 PG for administration to HIV-infected mice via oral gavage. An integrase strand transfer inhibitor (raltegravir) [ 22 ] and an attachment inhibitor (BMS-663068, 20 mg/kg b.w.) [ 23 ] were also included as a daily ART regimen.…”
Section: Concept Of Sechmentioning
confidence: 99%